Proposal to produce artisanal alcoholic beverages based on non-traditional exotic fruits such as cocona (solanum sessiliflorum), jack fruit (artocarpus heterophyllus) and salak (salacca zalacca). - Macas López, Cristina Alexandra; Medranda Vargas, Gema Narcisa; Peña Macías, Andrés David (Ingeniería Química y Desarrollo, 2024)
In Ecuador, three exotic fruits have been found that are not commercialized in the Ecuadorian market, due to the lack of knowledge on the part of the producers and consumers, that is why it has been motivated to elaborate a distilled and fermented liquor from the cocona, jack fruit and salad to promote consumption. 28 formulations with 3 types of yeasts are made, in addition the proportions of fruits, sugar and water are controlled, the latter are left to ferment with a time variant of 15 and 30 days at 20 ° C, then they are distilled to obtain a liquor with 27 Alcoholics An internal evaluation is carried out in which the sample 1411 is chosen due to its excellent organoleptic characteristics, according to the physicochemical analysis the sample lacks methanol, after that culinary proposals such as passion fruit mousse, naranjilla cocktail and chimichurri are made are carried out Acceptance test to 60 evaluators through hedonic scale. As a result, it was obtained that in general characteristics 58 evaluators extremely like passion fruit mousse, 56 extremely like cocktail and 58 extremely like chimichurri, no evaluator dislikes any of the preparations made, this result showed that it was possible.